Optimasi Polyvinilpyrolidone K-30 dan Sodium Starch Glycolate pada Tablet Likuisolid Simvastatin dengan Desain Faktorial - Nursatriya, Agne Yuliana; Sari, Lusia Oktora Ruma Kumala; Nurahmanto, Dwi (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
The liquisolid technique is one way to increase the drug dissolution rate, which has low solubility in water and can improve drug flow properties. This research aims to determine the optimum composition of a combination of polymer PVP K-30 and SSG on a liquisolid simvastatin tablet with a factorial design. The factorial design method is used to determine the effect of the concentration of two factors, namely PVP K-30 and SSG, on the response of hardness, friability, disintegration time, and dissolution. PVP K-30 acts as a binder, and SSG works as a disintegration, determines the optimum formula using expert design software version 1. The result showed that all formulas meet the requirements of hardness values (4-8 kg), friability (<1%), disintegration time of no more than 15 minutes, and dissolution in 30 minutes. The use of PVP K-30 concentration of 6 mg and SSG 24 mg indicated the optimum formula with a desirability value of 0,806.